Decoupled hydrogen evolution from water/seawater splitting by integrating ethylene glycol oxidation on PtRh0.02@Rh nanowires with Rh atom modification. Issue 38 (8th September 2022) - Jiang, Xue; Dong, Zemeng; Zhang, Qiong; Xu, Guang-Rui; Lai, Jianping; Li, Zhenjiang; Wang, Lei
Abstract : PtRh nanowires with sub-monolayer of Rh atoms on the surface (PtRh0.02 @Rh NWs) are fabricated and facilitate both hydrogen evolution reaction and ethylene glycol evolution reaction owing to the tensile strain and large electrocatalytic active surface area. Abstract : The electrochemical oxidation of ethylene glycol (EG), which is favorable for replacing the sluggish oxygen evolution reaction (OER) in thermodynamics, realizes energy-saving hydrogen evolution and also produces high-value chemical products of glycolic acid. Under the guidance of this concept, PtRh nanowires with Rh atom modification (PtRh0.02 @Rh NWs), which exhibited excellent properties during the hydrogen evolution reaction (HER) and ethylene glycol evolution reaction (EGOR), were designed and synthesized by controlling the reduction rate of metal precursor through a simple one-step solvothermal reduction. The interface strain effect produced by the metal co-doping effectively adjusted the electronic structure, contributing to introducing the heteroatom active center and inducing lattice strain, thereby achieving excellent electrocatalytic performance. The obtained PtRh0.02 @Rh NWs exhibited excellent HER property with an extremely low overpotential of 30.6 and 45.8 mV, and Tafel slope of 39.1 and 39.5 mV dec −1 in alkaline water and seawater electrolytes, respectively, as well as outstanding EGOR properties with peak current density of 1.25 and 1.17 A mg −1, respectively. Additionally, the PtRh0.02 @Rh NWs showed superior stability compared to that of commercial platinum black obtained from Johnson Matthey Corporation (JM-Pt black). When using PtRh0.02 @Rh NWs as biofunctional materials for the HER in the cathode and the EGOR in the anode, a cell voltage of only 0.66 V for PtRh0.02 @Rh NWs (HER)‖PtRh0.02 @Rh NWs (EGOR) achieved a current density of 10 mA cm −2, which was much smaller than that of PtRh0.02 @Rh NWs (HER)‖PtRh0.02 @Rh NWs (OER) at 1.57 V. The results of electrochemical in situ Fourier transform infrared (FTIR) spectroscopy showed that the synthesized PtRh0.02 @Rh NWs promoted the production of high-value glycolic acid when EG was dehydrogenated to form C2 intermediates. The Rh atoms modified on the surface of the Pt nanowires provided an effective strain effect to optimize the active sites, which creates a universal strategy for the design of highly efficient and durable bifunctional catalysts.